Effects of elevated pCO2 on the metabolism of a temperate rhodolith Lithothamnion corallioides grown under different temperatures. Issue 4 (28th June 2013) - Noisette, Fanny; Duong, Gwendoline; Six, Christophe; Davoult, Dominique; Martin, Sophie; Hurd, C.
<x xml:space="preserve">Abstract</x> Coralline algae are considered among the most sensitive species to near future ocean acidification. We tested the effects of elevated pCO2 on the metabolism of the free‐living coralline alga Lithothamnion corallioides ("maerl") and the interactions with changes in temperature. Specimens were collected in North Brittany (France) and grown for 3 months at pCO2 of 380 (ambient pCO2), 550, 750, and 1000 μatm (elevated pCO2) and at successive temperatures of 10°C (ambient temperature in winter), 16°C (ambient temperature in summer), and 19°C (ambient temperature in summer +3°C). At each temperature, gross primary production, respiration (oxygen flux), and calcification (alkalinity flux) rates were assessed in the light and dark. Pigments were determined by HPLC. Chl a, carotene, and zeaxanthin were the three major pigments found in L. corallioides thalli. Elevated pCO2 did not affect pigment content while temperature slightly decreased zeaxanthin and carotene content at 10°C. Gross production was not affected by temperature but was significantly affected by pCO2 with an increase between 380 and 550 μatm. Light, dark, and diel (24 h) calcification rates strongly decreased with increasing pCO2 regardless of the temperature. Although elevated pCO2 only slightly affected gross production in L. corallioides, diel net calcification was reduced by up to 80% under the 1, 000 μatm treatment. Our findings suggested that near future levels of CO2 will have profound consequences for carbon and carbonate budgets in rhodolith beds and for the sustainability of these habitats.